Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

Pathological drivers of coral diseases across the Arabian Peninsula - Thierry M. Work; Greta S. Aeby; David Abrego; Jessica Bouwmeester; Emily Howells; Pedro Range; Maren Ziegler; Thor Jensen; Amanda Shore; Grace Vaughan; John A. Burt; Christian R. Voolstra; et al. (Coral Reefs, 2026)
Increasing trends of coral mortality are a challenge to coral reef management worldwide, and a need exists to identify the causes and pathways involved. Pathology is useful to help decipher potential causes of mortality in animals, because it illuminates agents associated with lesions and gives insights on the nature of how a host responds to said agents. To better understand the nature of threats facing corals in the Arabian Peninsula, we performed gross and microscopic pathology on corals from Saudi Arabia, Qatar, and the United Arab Emirates. Among 321 coral fragments examined from 21 genera, tissue loss was the most common lesion seen in 31% of samples, reflecting its widespread presence on reefs from the Arabian Peninsula. Histologically, 68% of lesions exhibited necrosis, predominantly in the basal body wall and surface body wall. Endolithic filamentous microalgae and sponges, originating from the skeleton, were associated with 57% and 39% of lesions, respectively, and were often linked to necrosis and hyaline membrane formation. Cell-associated microbial aggregates and coccidia were detected mainly in Acropora, Pocillopora , and Porites but were not associated with adverse host response. Notably, 69–100% of fragments showing lesions were female likely reflecting the temporal reproductive life history of corals in the region. Our findings highlight endolithic organisms as major contributors to coral tissue degradation in the Arabian Peninsula. Future studies might focus on drivers of endolithic microalgal and sponge dynamics in the region and their role in coral reef health.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Licence to predict – Investigating approaches to modelling low-occurrence deep-sea Irish Antipatharia with a new evaluation metric - ALEXA PARIMBELLI; MARK P. JOHNSON; KERRY HOWELL; CLAIRE LAGUIONIE-MARCHAIS; A. LOUISE ALLCOCK (Mediterranean Marine Science, 2025)
Species distribution modelling has proven effective in locating cold-water coral hotspots in the deep sea. Maximum entropy (MaxEnt) and gradient boosting (GBM) are equally good at modelling rare species, but previous efforts to predict the distribution of deep-sea Antipatharia have mostly employed MaxEnt. This study investigates how algorithm choice (MaxEnt or GBM) and the application of backward stepwise variable pre-selection influence model performance and generalisation. Thirty-six models (four frameworks for nine black coral morphospecies) were built and evaluated using AUC, TSS, and the average TSS index (ATI), a novel metric that calculates TSS drops between training and test data to measure generalisation capability.ATI identified concerns in model generalisation that were not captured by AUC and TSS, making it a valuable tool for evaluating predictive model quality in conservation applications. MaxEnt outperformed GBM in predicting black coral distribution, and the pre-selection of variables did not improve performance. Satisfactory results were only obtained for the two MaxEnt models of Stichopathes gravieri, providing insights into the implications of using small datasets in conservation efforts. The inconsistencies in our findings do not lead us to recommend the use of a single model type in future studies; rather, we stress the importance of careful evaluation of model metrics with ecological knowledge of the species distribution when applying a dataset to conservation purposes.

Observation error appears to explain the perception of earlier maturation in Atlantic cod following the industrialised fishing - Olav Sigurd Kjesbu; Ine Elise Moksness; Shuyang Ma; Jennifer A. Devine; Maud Alix; Johanna Fall; Côme Denechaud; Thassya C. dos Santos Schmidt; Anders Thorsen; Geir Huse; Daniel Howell; Knut Korsbrekke (Progress in Oceanography, 2025)

Regional differentiation in somatic growth and maturation attributes for loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Larisa Avens; Margaret M. Lamont; Allen M. Foley; Benjamin M. Higgins; Lyndsey N. Howell; Gretchen Lovewell; Donna J. Shaver; Brian A. Stacy; J. Shelby Walker; Jamie M. Clark; Amy A. Wallace; Hannah B. Vander Zanden (Marine Biology, 2025)

Rapamycin Treatment Reduces Brain Pericyte Constriction in Ischemic Stroke - Daniel J. Beard; Lachlan S. Brown; Gary P. Morris; Yvonne Couch; Bryan A. Adriaanse; Christina Simoglou Karali; Anna M. Schneider; David W. Howells; Zoran B. Redzic; Brad A. Sutherland; Alastair M. Buchan (Translational Stroke Research, 2025)
The contraction and subsequent death of brain pericytes may play a role in microvascular no-reflow following the reopening of an occluded artery during ischemic stroke. Mammalian target of rapamycin (mTOR) inhibition has been shown to reduce motility/contractility of various cancer cell lines and reduce neuronal cell death in stroke. However, the effects of mTOR inhibition on brain pericyte contraction and death during ischemia have not yet been investigated. Cultured pericytes exposed to simulated ischemia for 12 h in vitro contracted after less than 1 h, which was about 7 h prior to cell death. Rapamycin significantly reduced the rate of pericyte contraction during ischemia; however, it did not have a significant effect on pericyte viability at any time point. Rapamycin appeared to reduce pericyte contraction through a mechanism that is independent of changes in intracellular calcium. Using a mouse model of middle cerebral artery occlusion, we showed that rapamycin significantly increased the diameter of capillaries underneath pericytes and increased the number of open capillaries 30 min following recanalisation. Our findings suggest that rapamycin may be a useful adjuvant therapeutic to reduce pericyte contraction and improve cerebral reperfusion post-stroke.

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Development and application of a genetic baseline to inform bull trout (Salvelinus confluentus) passage and conservation in the Snake River - John S. Hargrove; Thomas A. Delomas; Matthew R. Campbell; Philip J. Howell; Audrey C. Harris; Richard Wilkison (Conservation Genetics, 2025)

Analysis of facies proportions as a tool to quantify reservoir heterogeneity - Kachalla Aliyuda; Dimitrios Charlaftis; Charlotte Priddy; John A. Howell (Marine and Petroleum Geology, 2024)

An eight-founder wheat MAGIC population allows fine-mapping of flowering time loci and provides novel insights into the genetic control of flowering time - Laure Fourquet; Tobias Barber; Camila Campos-Mantello; Phil Howell; Beata Orman-Ligeza; Lawrence Percival-Alwyn; Gemma A. Rose; Hester Sheehan; Tally I. C. Wright; Friedrich Longin; Tobias Würschum; Dario Novoselovic; et al. (Theoretical and Applied Genetics, 2024)
Flowering time synchronizes reproductive development with favorable environmental conditions to optimize yield. Improved understanding of the genetic control of flowering will help optimize varietal adaptation to future agricultural systems under climate change. Here, we investigate the genetic basis of flowering time in winter wheat ( Triticum aestivum L.) using an eight-founder multi-parent advanced generation intercross (MAGIC) population. Flowering time data was collected from field trials across six growing seasons in the United Kingdom, followed by genetic analysis using a combination of linear modelling, simple interval mapping and composite interval mapping, using either single markers or founder haplotype probabilities. We detected 57 quantitative trait loci (QTL) across three growth stages linked to flowering time, of which 17 QTL were identified only when the major photoperiod response locus Ppd-D1 was included as a covariate. Of the 57 loci, ten were identified using all genetic mapping approaches and classified as ‘major’ QTL, including homoeologous loci on chromosomes 1B and 1D, and 4A and 4B. Additional Earliness per se flowering time QTL were identified, along with growth stage- and year-specific effects. Furthermore, six of the main-effect QTL were found to interact epistatically with Ppd-D1 . Finally, we exploited residual heterozygosity in the MAGIC recombinant inbred lines to Mendelize the Earliness per se QTL QFt.niab-5A.03 , which was confirmed to modulate flowering time by at least four days. This work provides detailed understanding of the genetic control of phenological variation within varieties relevant to the north-western European wheat genepool, aiding informed manipulation of flowering time in wheat breeding.

Quantifying Virtual Field Trip Efficiency - J. H. Pugsley; J. A. Howell; A. J. Hartley; S. J. Buckley; M. Chmielewska; N. Naumann; N. J. Schofield; R. Brackenridge (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)
The efficiency of virtual field trips (VFTs) compared to their physical counterparts, is often regarded as one of their key benefits. Virtual field trips are typically more time, cost and environmentally efficient and logistically easier to plan and execute. This is largely due to the lack of travel, however, the nature of these efficiencies, which is essential for deciding whether a trip should be virtual, physical or blended, have not previously been quantified. Here we present a quantitative evaluation of several measures of efficiency, using data from a like-for-like comparison between 10 day long virtual and physical field trips to Utah, USA, from the University of Aberdeen, UK. For this case study, our results demonstrate that virtual field trips are more efficient across all the categories of time, cost, environmental impact, and logistics. In addition to saved air travel days at the start and end of the physical trip, a further 33.3% of the time on the physical field trip was spent travelling (walking and driving). This time saving allowed an additional 16 localities to be visited on the virtual field trip. The virtual field trip localities also ran in an order that best suited the geological narrative rather than their geographic location which the physical field trip was restricted by. Flights and driven kilometres for the physical trip produced c. 4 t of carbon dioxide equivalent (CO 2 ) per student. The virtual trip produce <1% of the CO 2 and was comparable to a typical teaching week, making it significantly more environmentally efficient. The cost of the virtual trip was negligible compared to that of the physical trip (saving up to £ 3000 GBP per student). These findings were compared to the fulfilment of learning outcomes, quantified primarily through questionnaires, the student responses suggest that the PFT and VFT perceptions of learning outcomes were generally comparable. Efficiency is not the only measure of a successful field trip, with other parameters such as social cohesion and embodiment within the outdoor environment that must also be considered when planning a field trip. Therefore, the authors do not advocate or support an abandonment of physical field trips. Rather, this study aims to provide a first attempt to quantify efficiency to inform decision making when planning field training.

Corrigendum to “Plutonium and other radionuclides persist across marine-to-terrestrial ecotopes in the Montebello Islands sixty years after nuclear tests” [Sci. Total Environ. Volume 691, 15 November 2019, pages 572–583] - M.P. Johansen; D.P. Child; T. Cresswell; J.J. Harrison; M.A.C. Hotchkis; N.R. Howell; A. Johansen; S. Sdraulig; S. Thiruvoth; E. Young; S.D. Whiting (Science of The Total Environment, 2024)

Understanding the petrophysical properties, seismic responses and impacts of the basalt-sediment transition in prospective sedimentary basins - Natália Famelli; John Millett; Malcolm Hole; Dougal A. Jerram; Leonardo C. de Oliveira; Evandro F. Lima; Isabela de O. Carmo; Sverre Planke; Jessica H. Pugsley; Magda Chmielewska; John A. Howell; David W. Jolley (Journal of South American Earth Sciences, 2024)

Avian community responses to energy development and woody encroachment - John M. Yeiser; Paige E. Howell; Anna M. Matthews; Gregory T. Wann; Jim Giocomo; James A. Martin (Biological Conservation, 2024)

An Integrative Approach to Weight Management – Patient-centered Medical Home, Wellness Center, and Pharmacology - M. Coy; S. Troxell; B. Roper; K. Russo; O. Erinne; A. Luker; S. Shalak; J. Howell; J. Duhart (Journal of the Academy of Nutrition and Dietetics, 2024)

Transcriptomic analyses during development reveal mechanisms of integument structuring and color production - Adam M. M. Stuckert; Layla Freeborn; Kimberly A. Howell; Yusan Yang; Rasmus Nielsen; Corinne Richards-Zawacki; Matthew D. MacManes (Evolutionary Ecology, 2024)
Skin coloration and patterning play a key role in animal survival and reproduction. As a result, color phenotypes have generated intense research interest. In aposematic species, color phenotypes can be important in avoiding predation and in mate choice. However, we still know little about the underlying genetic mechanisms of color production, particularly outside of a few model organisms. Here we seek to understand the genetic mechanisms underlying the production of different colors and how these undergo shifting expression patterns throughout development. To answer this, we examine gene expression of two different color patches(yellow and green) in a developmental time series from young tadpoles through adults in the poison frog Oophaga pumilio. We identified six genes that were differentially expressed between color patches in every developmental stage ( casq1, hand2, myh8, prva, tbx3, and zic1). Of these, hand2, myh8, tbx3, and zic1 have either been identified or implicated as important in coloration in other taxa. Casq1 and prva buffer Ca 2+ and are a Ca 2+ transporter, respectively, and may play a role in preventing autotoxicity to pumiliotoxins, which inhibit Ca 2+ -ATPase activity. We identify further candidate genes (e.g., adh, aldh1a2, asip, lef1, mc1r, tyr, tyrp1, xdh ), and identify a suite of hub genes that likely play a key role in integumental reorganization during development (e.g., collagen type I–IV genes, lysyl oxidases) which may also affect coloration via structural organization of chromatophores that contribute to color and pattern. Overall, we identify the putative role of a suite of candidate genes in the production of different color types in a polytypic, aposematic species.

Diverse and ecologically unique mesophotic coral ecosystems in the central Indian Ocean - C. Diaz; K. L. Howell; P. Hosegood; A. Bolton; N. L. Foster (Coral Reefs, 2024)
Research on Mesophotic Coral Ecosystems (MCEs; 30–150 m) has grown exponentially in the last few decades, highlighting their rich diversity and extensive distribution. However, they are still largely underexplored compared to shallow-water coral reefs and frequently remain under-protected and under-represented in marine spatial planning. One reason for the imbalance between the high ecological value of MCEs and the limited levels of protection may be that baseline data on MCEs are largely missing to date, yet are crucial to provide evidence-based information for management actions. Here, we present data on the alpha and beta diversity of the benthic communities within MCEs in the Chagos Archipelago, Indian Ocean. Using imagery collected from Remotely Operated Vehicle surveys, benthic invertebrate megafauna were surveyed along the entire depth gradient from shallow to lower mesophotic depths (15–160 m). The diversity of the benthic communities decreased with increasing depth, from shallow water to the lower mesophotic zone. Nevertheless, the deepest parts of MCEs in the Archipelago displayed higher species richness values than several other shallow subtropical regions. In addition, the benthic communities showed high dissimilarity along the depth gradient, indicating that the key driver of community composition change with depth is species turnover (species replacement), revealing the uniqueness of MCEs. This study presents novel findings on MCEs in the central Indian Ocean, demonstrating that they host a high and unique benthic diversity, and highlighting the need to protect these ecosystems to preserve the overall biodiversity of coral reefs.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Relationship Between a High-Fat Diet, Reduced Mobility, and Trace Element Overload in the Olfactory Bulbs of C57BL/6J and DBA/2J Mice - Melissa S. Totten; Jenna M. Howell; Jordan A. Tomberlin; Keith M. Erikson (Biological Trace Element Research, 2024)

A new winter wheat genetic resource harbors untapped diversity from synthetic hexaploid wheat - Tally I. C. Wright; Richard Horsnell; Bethany Love; Amanda J. Burridge; Keith A. Gardner; Robert Jackson; Fiona J. Leigh; Aleksander Ligeza; Sigrid Heuer; Alison R. Bentley; Philip Howell (Theoretical and Applied Genetics, 2024)
Key message The NIAB_WW_SHW_NAM population, a large nested association mapping panel, is a useful resource for mapping QTL from synthetic hexaploid wheat that can improve modern elite wheat cultivars. Abstract The allelic richness harbored in progenitors of hexaploid bread wheat ( Triticum aestivum L.) is a useful resource for addressing the genetic diversity bottleneck in modern cultivars. Synthetic hexaploid wheat (SHW) is created through resynthesis of the hybridisation events between the tetraploid ( Triticum turgidum subsp. durum Desf.) and diploid ( Aegilops tauschii Coss.) bread wheat progenitors. We developed a large and diverse winter wheat nested association mapping (NAM) population (termed the NIAB_WW_SHW_NAM) consisting of 3241 genotypes derived from 54 nested back-cross 1 (BC 1 ) populations, each formed via back-crossing a different primary SHW into the UK winter wheat cultivar ‘Robigus’. The primary SHW lines were created using 15 T. durum donors and 47 Ae. tauschii accessions that spanned the lineages and geographical range of the species. Primary SHW parents were typically earlier flowering, taller and showed better resistance to yellow rust infection ( Yr ) than ‘Robigus’. The NIAB_WW_SHW_NAM population was genotyped using a single nucleotide polymorphism (SNP) array and 27 quantitative trait loci (QTLs) were detected for flowering time, plant height and Yr resistance. Across multiple field trials, a QTL for Yr resistance was found on chromosome 4D that corresponded to the Yr28 resistance gene previously reported in other SHW lines. These results demonstrate the value of the NIAB_WW_SHW_NAM population for genetic mapping and provide the first evidence of Yr28 working in current UK environments and genetic backgrounds. These examples, coupled with the evidence of commercial wheat breeders selecting promising genotypes, highlight the potential value of the NIAB_WW_SHW_NAM to variety improvement.

Global mitochondrial and chloroplast genome diversity in the threatened aquatic carnivorous plant Aldrovanda vesiculosa - Helena Štorchová; Manuela Krüger; Ian Small; Lubomír Adamec; Paul G. Nevill; Katharine A. Howell; Kingsley W. Dixon; Mark Derbyshire; Xiao Zhong; Adam T. Cross (Aquatic Botany, 2024)

Black-and-white pelage as visually protective coloration in colobus monkeys - Ossi Nokelainen; Sandra Winters; Zeke Rowe; Fernando A. Campos; Eva C. Wikberg; Natasha Howell; Tim Caro (Behavioral Ecology and Sociobiology, 2024)
Conspicuous coloration is often seen as the evolutionary consequence of either sexual selection or warning predators visually about prey defences, although not all conspicuous species fit this paradigm. Exceptions include several species of colobus monkeys whose black-and-white coloration, characteristic of larger colobines, has never been explained. Here, using photographs of black-and-white colobus ( Colobus vellerosus ) taken in the wild, quantitative image analysis, and vision modelling (acuity-corrected feline, chimpanzee, and raptor vision), we provide evidence that their coloration provides distance-dependent camouflage in natural forest environments. At all viewing distances, black-and-white colobus monkeys blend into their environment because of their high chromatic overlap with the background when viewed by ecologically relevant predator vision models which have low visual acuities. Additionally, for chimpanzee and felid vision, there was evidence of edge disruption at longer viewing distances. Our comparative analyses of different species of colobines do not support an association between black-and-white coloration and larger body mass or group size, but this may simply be due to the limited number of species within the family. We reason that black-and-white colobines gain visually protective coloration through background matching against felids, and also benefit through disruptive coloration against felids and chimpanzees but rely on these protective coloration mechanisms less against raptors. Significance statement Conspicuous black-and-white coloration in colobus monkeys has long eluded an evolutionary explanation. Our research, employing photographs of colobus monkeys, image analysis, and vision modelling, unveils a novel approach to this coloration. We show that in their natural forest habitats, black-and-white colobus monkeys employ distance-dependent camouflage against ecologically relevant predators with low visual acuity, blending in with the background at increasing viewing distances. In summary, the evolution of black-and-white colobus coloration appears to be related to background matching against felids, with added benefits of disruptive camouflage against felids and chimpanzees, less so to raptors, offering fresh insights into the complex interplay of coloration and survival strategies in mammals.

A risk assessment for the remote ocean: the case of the South East Atlantic - Holly J. Niner; Siân E. Rees; Giulia La Bianca; Kirsty A. McQuaid; Kerry L. Howell (Frontiers in Marine Science, 2024)
Degradation of the natural world and associated ecosystem services is attributed to a historical failure to include its ‘value’ in decision-making. Uncertainty in the quantification of the relationship between natural capital ‘assets’ that give rise to critical societal benefits and people is one reason for the omission of these values from natural resource management. As this uncertainty increases in marine systems and further still with distance from the coast, the connection between society and natural capital assets is less likely to be included adequately in decision-making. Natural capital assets of Areas Beyond National Jurisdiction (ABNJ), including those of the deep sea, are distant but are known to generate many benefits for society, from the diffuse and broad-scale benefits of climate regulation to the provision of wild fish for food. While our understanding of the precise relationships (the status of asset stocks, ecosystem functions and processes) that control the availability of ecosystem services and the flows of benefits is limited, this does not preclude opening a discourse on how these natural capital assets could best be managed to continue to benefit society. Here we apply a natural capital approach to the South East Atlantic ABNJ, one of the least scientifically understood regions of the planet, and develop a framework for risk assessment. We do this by describing the benefit flows from the natural capital assets of the region, appraising how activities are creating pressures on these flows and whether the controls for these pressures protect them. Our risk register highlights how governance currently favours the protection of direct (extractive) benefit flows from natural capital assets of the region, which are primarily targeted for financial benefit. Without a systems-based framework that can account for the cumulative pressures on natural capital assets their status, associated ecosystem services and benefits are at risk. Such an approach is essential to capture and protect the foundational and often diffuse connections between marine natural capital and global society.

Ciguatera poisoning in French Polynesia: A review of the distribution and toxicity of Gambierdiscus spp., and related impacts on food web components and human health - M. Chinain; C. Gatti Howell; M. Roué; A. Ung; K. Henry; T. Revel; P. Cruchet; J. Viallon; H.T. Darius (Harmful Algae, 2023)

Correction to: The Effects of Long-term, Low-dose β-N-methylamino-L-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

The Effects of Long-term, Low-dose β-N-methylamino-l-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

A standardised ecosystem services framework for the deep sea - Giulia La Bianca; Sian Rees; Martin J. Attrill; Amanda T. Lombard; Kirsty A. McQuaid; Holly J. Niner; Henk van Rein; Kerry J. Sink; Kerry L. Howell (Frontiers in Marine Science, 2023)
Despite its remoteness, human activity has impacted the deep sea and changes to the structure and function of deep-sea ecosystems are already noticeable. In terrestrial and shallow water marine environments, demonstrating how ecosystems support human well-being has been instrumental in setting policy and management objectives for sustainable resource use. Foundational to this approach is a framework of ecosystem service (ES) classification and a synthesis of the knowledge base, which can then be used to structure decision-support tools such as ecosystem accounts or Environmental Impact Assessments. At present, no such framework exists for the deep sea. There is thus an urgent need to determine and assess the ES provided by deep-sea habitats and species before (potentially irreversible) decisions are made about deep-sea habitat use and governance. As a first step towards the incorporation of ES in such decision-making, we undertake two systematic reviews of the scientific literature based on the principles of the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) systematic process. This was to define a comparative ES framework and synthesise the current evidence base for how deep-sea habitats support ecosystem services. Our framework proposes four supporting services, three regulating services, four provisioning services and three cultural services for which there is an established and growing body of evidence for the role of deep-sea habitats. The ES framework presented here provides a structure for deep-sea ecosystem services. In its next phase of development, this could provide the foundation for the development of habitat-ecosystem service matrices, which are a critical component for truly accounting for ES in decision-making, particularly spatial management. This framework has significant implications for deep-sea management, conservation and policy, as it provides an ecosystem services-based tool that can be used in any deep-sea ecosystems management across the planet, and it also shows how critical these data gaps are for today’s decisions and how seriously they should be considered in decision-making processes.

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Diversity and transparency in gynecologic oncology clinical trials - Mary Katherine Montes de Oca; Elizabeth P. Howell; Daniel Spinosa; Hope Knochenhauer; Benjamin J. Peipert; Eric Severson; Shakti Ramkissoon; Tomi F. Akinyemiju; Rebecca A. Previs (Cancer Causes & Control, 2023)

Communicating Effectively via Tele-oncology (Comskil TeleOnc): a Guide for Best Practices for Communication Skills in Virtual Cancer Care - Smita C. Banerjee; Jessica M. Staley; Frances Howell; Charlotte Malling; Aimee Moreno; Chris Kotsen; Dhwani Parikh; Patricia A. Parker (Journal of Cancer Education, 2022)

How thermal challenges change gene regulation in the songbird brain and gonad: Implications for sexual selection in our changing world - Sara E. Lipshutz; Clara R. Howell; Aaron M. Buechlein; Douglas B. Rusch; Kimberly A. Rosvall; Elizabeth P. Derryberry (Molecular Ecology, 2022)
In a rapidly warming world, exposure to high temperatures may impact fitness, but the gene regulatory mechanisms that link sublethal heat to sexually selected traits are not well understood, particularly in endothermic animals. Our experiment used zebra finches ( Taeniopygia guttata ), songbirds that experience extreme temperature fluctuations in their native Australia. We exposed captive males to an acute thermal challenge (43°C) compared with thermoneutral (35°C) and lower (27°C) temperatures. We found significantly more heat dissipation behaviours at 43°C, a temperature previously shown to reduce song production and fertility, and more heat retention behaviours at 27°C. Next, we characterized transcriptomic responses in tissues important for mating effort—the posterior telencephalon, for its role in song production, and the testis, for its role in fertility and hormone production. Differential expression of hundreds of genes in the testes, but few in the brain, suggests the brain is less responsive to extreme temperatures. Nevertheless, gene network analyses revealed that expression related to dopaminergic signalling in the brain covaried with heat dissipation behaviours, providing a mechanism by which temporary thermal challenges may alter motivational circuits for song production. In both brain and testis, we observed correlations between thermally sensitive gene networks and individual differences in thermoregulatory behaviour. Although we cannot directly relate these gene regulatory changes to mating success, our results suggest that individual variation in response to thermal challenges could impact sexually selected traits in a warming world.

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

Impact of home food production on nutritional blindness, stunting, wasting, underweight and mortality in children: a systematic review and meta-analysis of controlled trials - Chizoba Bassey; Harriet Crooks; Katherine Paterson; Rachel Ball; Kristoffer Howell; Iona Humphries-Cuff; Kirsty Gaffigan; Nitya Rao; Jennifer A. Whitty; Lee Hooper (Critical Reviews in Food Science and Nutrition, 2022)

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

A Review of Applications Evaluating Fisheries Management Scenarios through Marine Ecosystem Models - H. A. Perryman; C. Hansen; D. Howell; E. Olsen (Reviews in Fisheries Science & Aquaculture, 2021)

A dry future for the Everglades favors invasive herpetofauna - Hunter J. Howell; Giacomo L. Delgado; Alyssa C. Wood; Leila M. Thompson; Eric A. Cline; Christopher A. Searcy (Biological Invasions, 2021)

Physiological diversity among sympatric, conspecific endosymbionts of coral (Cladocopium C1acro) from the Great Barrier Reef - V. H. Beltrán; E. Puill-Stephan; E. Howells; A. Flores-Moya; M. Doblin; E. Núñez-Lara; V. Escamilla; T. López; M. J. H. van Oppen (Coral Reefs, 2021)

Evaluation of Dosing Strategies of N-acetylcysteine for Acetaminophen Toxicity in Patients Greater than 100 Kilograms: Should the Dosage Cap Be Used? - Regan A. Baum; Jordan A. Woolum; Abby M. Bailey; Molly M. Howell; Kyle A. Weant; LeeAnn Geraghty; Sanjay Mohan; Ashley N. Webb; Mark K. Su; Peter Akpunonu; Adam J. Dugan; Leanne Atchison; et al. (Journal of Medical Toxicology, 2021)

Accommodating the role of site memory in dynamic species distribution models - Graziella V. DiRenzo; David A. W. Miller; Blake R. Hossack; Brent H. Sigafus; Paige E. Howell; Erin Muths; Evan H. C. Grant (Ecology, 2021)
First‐order dynamic occupancy models (FODOMs) are a class of state‐space model in which the true state (occurrence) is observed imperfectly. An important assumption of FODOMs is that site dynamics only depend on the current state and that variations in dynamic processes are adequately captured with covariates or random effects. However, it is often difficult to understand and/or measure the covariates that generate ecological data, which are typically spatiotemporally correlated. Consequently, the non‐independent error structure of correlated data causes underestimation of parameter uncertainty and poor ecological inference. Here, we extend the FODOM framework with a second‐order Markov process to accommodate site memory when covariates are not available. Our modeling framework can be used to make reliable inference about site occupancy, colonization, extinction, turnover, and detection probabilities. We present a series of simulations to illustrate the data requirements and model performance. We then applied our modeling framework to 13 yr of data from an amphibian community in southern Arizona, USA. In this analysis, we found residual temporal autocorrelation of population processes for most species, even after accounting for long‐term drought dynamics. Our approach represents a valuable advance in obtaining inference on population dynamics, especially as they relate to metapopulations.

Using Habitat Classification to Assess Representativity of a Protected Area Network in a Large, Data-Poor Area Targeted for Deep-Sea Mining - Kirsty A. McQuaid; Martin J. Attrill; Malcolm R. Clark; Amber Cobley; Adrian G. Glover; Craig R. Smith; Kerry L. Howell (Frontiers in Marine Science, 2020)
Extractive activities in the ocean are expanding into the vast, poorly studied deep sea, with the consequence that environmental management decisions must be made for data-poor seafloor regions. Habitat classification can support marine spatial planning and inform decision-making processes in such areas. We present a regional, top–down, broad-scale, seafloor-habitat classification for the Clarion-Clipperton Fracture Zone (CCZ), an area targeted for future polymetallic nodule mining in abyssal waters in the equatorial Pacific Ocean. Our classification uses non-hierarchical, k-medoids clustering to combine environmental correlates of faunal distributions in the region. The classification uses topographic variables, particulate organic carbon flux to the seafloor, and is the first to use nodule abundance as a habitat variable. Twenty-four habitat classes are identified, with large expanses of abyssal plain and smaller classes with varying topography, food supply, and substrata. We then assess habitat representativity of the current network of protected areas (called Areas of Particular Environmental Interest) in the CCZ. Several habitat classes with high nodule abundance are common in mining exploration claims, but currently receive little to no protection in APEIs. There are several large unmanaged areas containing high nodule abundance on the periphery of the CCZ, as well as smaller unmanaged areas within the central CCZ, that could be considered for protection from mining to improve habitat representativity and safeguard regional biodiversity.

Effects of early life stress on cocaine intake in male and female rhesus macaques - Alison G. P. Wakeford; Brik Kochoian; Erin R. Siebert; Sarah Katznelson; Elyse L. Morin; Brittany R. Howell; Kai M. McCormack; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2020)

Knowledge of the Relationship Between Breastfeeding and Breast Cancer Risk Among Racial and Ethnic Minority Women - Jamilia R. Sly; Sarah J. Miller; Linda Thelemaque; Fahd Yazdanie; Rhoda Sperling; Fahimeh Sasan; Elizabeth A. Howell; Holly Loudon; Lina Jandorf (Journal of Cancer Education, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Annual outbreaks of coral disease coincide with extreme seasonal warming - E. J. Howells; G. O. Vaughan; T. M. Work; J. A. Burt; D. Abrego (Coral Reefs, 2020)

Localized outbreaks of coral disease on Arabian reefs are linked to extreme temperatures and environmental stressors - Greta Smith Aeby; Emily Howells; Thierry Work; David Abrego; Gareth J. Williams; Lisa M. Wedding; Jamie M. Caldwell; Monica Moritsch; John A. Burt (Coral Reefs, 2020)
The Arabian Peninsula borders the hottest reefs in the world, and corals living in these extreme environments can provide insight into the effects of warming on coral health and disease. Here, we examined coral reef health at 17 sites across three regions along the northeastern Arabian Peninsula (Persian Gulf, Strait of Hormuz and Oman Sea) representing a gradient of environmental conditions. The Persian Gulf has extreme seasonal fluctuations in temperature and chronic hypersalinity, whereas the other two regions experience more moderate conditions. Field surveys identified 13 coral diseases including tissue loss diseases of unknown etiology (white syndromes) in Porites, Platygyra , Dipsastraea , Cyphastrea, Acropora and Goniopora ; growth anomalies in Porites, Platygyra and Dipsastraea ; black band disease in Platygyra , Dipsastraea , Acropora, Echinopora and Pavona ; bleached patches in Porites and Goniopora and a disease unique to this region, yellow-banded tissue loss in Porites . The most widespread diseases were Platygyra growth anomalies (52.9% of all surveys), Acropora white syndrome (47.1%) and Porites bleached patches (35.3%). We found a number of diseases not yet reported in this region and found differential disease susceptibility among coral taxa. Disease prevalence was higher on reefs within the Persian Gulf (avg. 2.05%) as compared to reefs within the Strait of Hormuz (0.46%) or Oman Sea (0.25%). A high number of localized disease outbreaks (8 of 17 sites) were found, especially within the Persian Gulf (5 of 8 sites). Across all regions, the majority of variation in disease prevalence (82.2%) was associated with the extreme temperature range experienced by these corals combined with measures of organic pollution and proximity to shore. Thermal stress is known to drive a number of coral diseases, and thus, this region provides a platform to study disease at the edge of corals’ thermal range.

Use of standardized methods to improve extinction‐risk classification - Caitlin C. Mothes; Stephanie L. Clements; Dishane K. Hewavithana; Hunter J. Howell; Aaron S. David; Nicole D. Leventhal; Christopher A. Searcy (Conservation Biology, 2020)
Standardized classification methods based on quantifiable risk metrics are critical for evaluating extinction threats because they increase objectivity, consistency, and transparency of listing decisions. Yet, in the United States, neither federal nor state agencies use standardized methods for listing species for legal protection, which could put listing decisions at odds with the magnitude of the risk. We used a recently developed set of quantitative risk metrics for California herpetofauna as a case study to highlight discrepancies in listing decisions made without standardized methods. We also combined such quantitative metrics with classification tree analysis to attempt to increase the transparency of previous listing decisions by identifying the criteria that had inherently been given the most weight. Federally listed herpetofauna in California scored significantly higher on the risk‐metric spectrum than those not federally listed, whereas state‐listed species did not score any higher than species that were not state listed. Based on classification trees, state endemism was the most important predictor of listing status at the state level and distribution trend (decline in a species’ range size) and population trend (decline in a species’ abundance at localized sites) were the most important predictors at the federal level. Our results emphasize the need for governing bodies to adopt standardized methods for assessing conservation risk that are based on quantitative criteria. Such methods allow decision makers to identify criteria inherently given the most weight in determining listing status, thus increasing the transparency of previous listing decisions, and produce an unbiased comparison of conservation threat across all species to promote consistency, efficiency, and effectiveness of the listing process.

Corals in the hottest reefs in the world exhibit symbiont fidelity not flexibility - Emily J. Howells; Andrew G. Bauman; Grace O. Vaughan; Benjamin C. C. Hume; Christian R. Voolstra; John A. Burt (Molecular Ecology, 2020)
Reef‐building corals are at risk of extinction from ocean warming. While some corals can enhance their thermal limits by associating with dinoflagellate photosymbionts of superior stress tolerance, the extent to which symbiont communities will reorganize under increased warming pressure remains unclear. Here we show that corals in the hottest reefs in the world in the Persian Gulf maintain associations with the same symbionts across 1.5 years despite extreme seasonal warming and acute heat stress (≥35°C). Persian Gulf corals predominantly associated with Cladocopium (clade C) and most also hosted Symbiodinium (clade A) and/or Durusdinium (clade D). This is in contrast to the neighbouring and milder Oman Sea, where corals associated with Durusdinium and only a minority hosted background levels of Cladocopium . During acute heat stress, the higher prevalence of Symbiodinium and Durusdinium in bleached versus nonbleached Persian Gulf corals indicates that genotypes of these background genera did not confer bleaching resistance. Within symbiont genera, the majority of ITS2 rDNA type profiles were unique to their respective coral species, confirming the existence of host‐specific symbiont lineages. Notably, further differentiation among Persian Gulf sites demonstrates that symbiont populations are either isolated or specialized over tens to hundreds of kilometres. Thermal tolerance across coral species was associated with the prevalence of a single ITS2 intragenomic sequence variant (C3gulf), definitive of the Cladocopium thermophilum group. The abundance of C3gulf was highest in bleaching‐resistant corals and at warmer sites, potentially indicating a specific symbiont genotype (or set of genotypes) that may play a role in thermal tolerance that warrants further investigation. Together, our findings indicate that co‐evolution of host–Symbiodiniaceae partnerships favours fidelity rather than flexibility in extreme environments and under future warming.

Comparison of the Hepatotoxic Potential of Two Treatments for Autosomal-Dominant Polycystic Kidney DiseaseUsing Quantitative Systems Toxicology Modeling - J. L. Woodhead; L. Pellegrini; L. K. M. Shoda; B. A. Howell (Pharmaceutical Research, 2020)
Purpose Autosomal-dominant polycystic kidney disease (ADPKD) is an orphan disease with few current treatment options. The vasopressin V 2 receptor antagonist tolvaptan is approved in multiple countries for the treatment of ADPKD, however its use is associated with clinically significant drug-induced liver injury. Methods In prior studies, the potential for hepatotoxicity of tolvaptan was correctly predicted using DILIsym®, a quantitative systems toxicology (QST) mathematical model of drug-induced liver injury. In the current study, we evaluated lixivaptan, another proposed ADPKD treatment and vasopressin V 2 receptor antagonist, using DILIsym®. Simulations were conducted that assessed the potential for lixivaptan and its three main metabolites to cause hepatotoxicity due to three injury mechanisms: bile acid accumulation, mitochondrial dysfunction, and oxidative stress generation. Results of these simulations were compared to previously published DILIsym results for tolvaptan. Results No ALT elevations were predicted to occur at the proposed clinical dose for lixivaptan, in contrast to previously published simulation results for tolvaptan. As such, lixivaptan was predicted to have a markedly lower risk of hepatotoxicity compared to tolvaptan with respect to the hepatotoxicity mechanisms represented in DILIsym. Conclusions These results demonstrate the potential for using QST methods to differentiate drugs in the same class for their potential to cause hepatotoxicity.

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Balanced harvest: concept, policies, evidence, and management implications - Shijie Zhou; Jeppe Kolding; Serge M. Garcia; Michael J. Plank; Alida Bundy; Anthony Charles; Cecilie Hansen; Mikko Heino; Daniel Howell; Nis S. Jacobsen; David G. Reid; Jake C. Rice; et al. (Reviews in Fish Biology and Fisheries, 2019)

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

Variable responses of karst springs to recharge in the Middle Atlas region of Morocco - Brett A. Howell; Alan E. Fryar; Lahcen Benaabidate; Lhoussaine Bouchaou; Mohamed Farhaoui (Hydrogeology Journal, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Effects of ketamine treatment on cocaine-induced reinstatement and disruption of functional connectivity in unanesthetized rhesus monkeys - Eric A. Maltbie; Kaundinya S. Gopinath; Leonard L. Howell (Psychopharmacology, 2019)

Analyzing the Mechanisms Behind Macrolide Antibiotic-Induced Liver Injury Using Quantitative Systems Toxicology Modeling - Jeffrey L. Woodhead; Kyunghee Yang; David Oldach; Chris MacLauchlin; Prabhavathi Fernandes; Paul B. Watkins; Scott Q. Siler; Brett A. Howell (Pharmaceutical Research, 2019)

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Grain yield, evapotranspiration, and water-use efficiency of maize hybrids differing in drought tolerance - Baozhen Hao; Qingwu Xue; Thomas H. Marek; Kirk E. Jessup; Jacob D. Becker; Xiaobo Hou; Wenwei Xu; Edsel D. Bynum; Brent W. Bean; Paul D. Colaizzi; Terry A. Howell (Irrigation Science, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Correction to: The role of proteomics in the age of immunotherapies - Sarah A. Hayes; Stephen Clarke; Nick Pavlakis; Viive M. Howell (Mammalian Genome, 2018)

The role of proteomics in the age of immunotherapies - Sarah A. Hayes; Stephen Clarke; Nick Pavlakis; Viive M. Howell (Mammalian Genome, 2018)

Genomic and transcriptomic signals of thermal tolerance in heat‐tolerant corals ( Platygyra daedalea ) of the Arabian/Persian Gulf - Nathan L. Kirk; Emily J. Howells; David Abrego; John A. Burt; Eli Meyer (Molecular Ecology, 2018)
Scleractinian corals occur in tropical regions near their upper thermal limits and are severely threatened by rising ocean temperatures. However, several recent studies have shown coral populations can harbour genetic variation in thermal tolerance. Here, we have extended these approaches to study heat tolerance of corals in the Persian/Arabian Gulf, where heat‐tolerant local populations experience extreme summer temperatures (up to 36°C). To evaluate whether selection has depleted genetic variation in thermal tolerance, estimate potential future adaptive responses and understand the functional basis for these corals’ unusual heat tolerance, we conducted controlled crosses in the Gulf coral Platygyra daedalea . Heat tolerance is highly heritable in this population ( h 2 = 0.487–0.748), suggesting substantial potential for adaptive responses to selection for elevated temperatures. To identify genetic markers associated with this variation, we conducted genomewide SNP genotyping in parental corals and tested for relationships between paternal genotype and offspring thermal tolerance. Resulting multilocus SNP genotypes explained a large fraction of variation in thermal tolerance in these crosses (69%). To investigate the functional basis of these differences in thermal tolerance, we profiled transcriptional responses in tolerant and susceptible families, revealing substantial sire effects on transcriptional responses to thermal stress. We also studied sequence variation in these expressed sequences, identifying alleles and functional groups of differentially expressed genes associated with thermal tolerance. Our findings demonstrate that corals in this population harbour extensive genetic variation in thermal tolerance, and heat‐tolerant phenotypes differ in both gene sequences and transcriptional stress responses from their susceptible counterparts.

Species-specific nitrogenase activity in lichen-dominated biological soil crusts from the Colorado Plateau, USA - Terry J. Torres-Cruz; Armin J. Howell; Robin H. Reibold; Theresa A. McHugh; Mackenzie A. Eickhoff; Sasha C. Reed (Plant and Soil, 2018)

Species-Specific Coral Calcification Responses to the Extreme Environment of the Southern Persian Gulf - Emily J. Howells; Glenn Dunshea; Dain McParland; Grace O. Vaughan; Scott F. Heron; Morgan S. Pratchett; John A. Burt; Andrew G. Bauman (Frontiers in Marine Science, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Mechanisms of hepatotoxicity associated with the monocyclic β-lactam antibiotic BAL30072 - Franziska Paech; Simon Messner; Jochen Spickermann; Mathias Wind; Anne-Hortense Schmitt-Hoffmann; Anne Therese Witschi; Brett A. Howell; Rachel J. Church; Jeff Woodhead; Marc Engelhardt; Stephan Krähenbühl; Martina Maurer (Archives of Toxicology, 2017)

Variation in particulate C : N : P stoichiometry across the Lake Erie watershed from tributaries to its outflow - Clay Prater; Paul C. Frost; E. Todd Howell; Susan B. Watson; Arthur Zastepa; Sarah S. E. King; Richard J. Vogt; Marguerite A. Xenopoulos (Limnology and Oceanography, 2017)
Human activities can cause large alterations in biogeochemical cycles of key nutrients such as carbon (C), nitrogen (N), and phosphorus (P). However, relatively little is known about how these changes alter the proportional fluxes of these elements across ecosystem boundaries from rivers to lakes. Here, we examined environmental factors influencing spatial and temporal variation in particulate C : N : P ratios across the Lake Erie watershed from its tributaries to its outflow. Throughout the study, particulate nutrient ratios ranged widely (C : N 2.0–25.8, C : P 32–530, N : P 3.7–122.9), but mean values were generally lower than previous estimates from different aquatic environments. Particulate C : N ratios varied the least across all environments, but C : P and N : P ratios increased between tributaries and coastal areas and throughout the growing season in coastal environments. These ratios also differed temporally in offshore waters as particulate C : P and N : P were higher in the spring and summer and lower in the fall and winter. Particulate C : P ratios also increased between the western/central and eastern basins indicating differential nutrient processing across the lake. These stoichiometric changes were associated with unique environmental factors among ecosystems as tributary stoichiometry was related to terrestrial land use and land cover, coastal ratios were a product of mixing between riverine and offshore waters, and offshore patterns were influenced by differences in temperature and particulate nutrient loading among basins. Overall, by studying changes in particulate C : N : P ratios across the Lake Erie watershed, our study demonstrates the power of using mass balance principles to study nutrient transformations along the aquatic continuum.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Risk algorithms that include pathology adjustment for HER2 amplification need to make further downward adjustments in likelihood scores - D. G. Evans; E. R. Woodward; S. J. Howell; S. Verhoef; A. Howell; F. Lalloo (Familial Cancer, 2017)

Ecological Role of Submarine Canyons and Need for Canyon Conservation: A Review - Ulla Fernandez-Arcaya; Eva Ramirez-Llodra; Jacopo Aguzzi; A. Louise Allcock; Jaime S. Davies; Awantha Dissanayake; Peter Harris; Kerry Howell; Veerle A. I. Huvenne; Miles Macmillan-Lawler; Jacobo Martín; Lenaick Menot; et al. (Frontiers in Marine Science, 2017)

Complexity and health functionality of plant cell wall fibers from fruits and vegetables - A. Padayachee; L. Day; K. Howell; M. J. Gidley (Critical Reviews in Food Science and Nutrition, 2017)

Reduced glutamate in white matter of male neonates exposed to alcohol in utero: a 1H-magnetic resonance spectroscopy study - F. M. Howells; K. A. Donald; A. Roos; R. P. Woods; H. J. Zar; K. L. Narr; D. J. Stein (Metabolic Brain Disease, 2016)

Host adaptation and unexpected symbiont partners enable reef‐building corals to tolerate extreme temperatures - Emily J. Howells; David Abrego; Eli Meyer; Nathan L. Kirk; John A. Burt (Global Change Biology, 2016)
Understanding the potential for coral adaptation to warming seas is complicated by interactions between symbiotic partners that define stress responses and the difficulties of tracking selection in natural populations. To overcome these challenges, we characterized the contribution of both animal host and symbiotic algae to thermal tolerance in corals that have already experienced considerable warming on par with end‐of‐century projections for most coral reefs. Thermal responses in Platygyra daedalea corals from the hot Persian Gulf where summer temperatures reach 36°C were compared with conspecifics from the milder Sea of Oman. Persian Gulf corals had higher rates of survival at elevated temperatures (33 and 36°C) in both the nonsymbiotic larval stage (32–49% higher) and the symbiotic adult life stage (51% higher). Additionally, Persian Gulf hosts had fixed greater potential to mitigate oxidative stress (31–49% higher) and their Symbiodinium partners had better retention of photosynthetic performance under elevated temperature (up to 161% higher). Superior thermal tolerance of Persian Gulf vs. Sea of Oman corals was maintained after 6‐month acclimatization to a common ambient environment and was underpinned by genetic divergence in both the coral host and symbiotic algae. In P. daedalea host samples, genomewide SNP variation clustered into two discrete groups corresponding with Persian Gulf and Sea of Oman sites. Symbiodinium within host tissues predominantly belonged to ITS 2 rDNA type C3 in the Persian Gulf and type D1a in the Sea of Oman contradicting patterns of Symbiodinium thermal tolerance from other regions. Our findings provide evidence that genetic adaptation of both host and Symbiodinium has enabled corals to cope with extreme temperatures in the Persian Gulf. Thus, the persistence of coral populations under continued warming will likely be determined by evolutionary rates in both, rather than single, symbiotic partners.

Impacts of adaptation and responsibility framings on attitudes towards climate change mitigation - Rachel A. Howell; Stuart Capstick; Lorraine Whitmarsh (Climatic Change, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Generic reclassification and species boundaries in the rediscovered freshwater mussel ‘Quadrula’ mitchelli (Simpson in Dall, 1896) - John M. Pfeiffer III; Nathan A. Johnson; Charles R. Randklev; Robert G. Howells; James D. Williams (Conservation Genetics, 2016)

New furoquinoline alkaloid and flavanone glycoside derivatives from the leaves of Oricia suaveolens and Oricia renieri (Rutaceae) - Achille B. Nouga; Jean C. Ndom; Emmanuel M. Mpondo; Judith Caroline Ngo Nyobe; Alain Njoya; Luc M. Meva'a; Phillipa B. Cranwell; James A.S. Howell; Laurence M. Harwood; Jean Duplex Wansi (Natural Product Research, 2016)

Progress in neuroscience in Africa: editorial - Fleur M. Howells; V. A. Russell (Metabolic Brain Disease, 2016)

Alcohol exposure in utero is associated with decreased gray matter volume in neonates - Kirsten A. Donald; J. P. Fouche; Annerine Roos; Nastassja Koen; Fleur M. Howells; Edward P. Riley; Roger P. Woods; Heather J. Zar; Katherine L. Narr; Dan J. Stein (Metabolic Brain Disease, 2016)

Genetic predisposition and early life experience interact to determine glutamate transporter (GLT1) and solute carrier family 12 member 5 (KCC2) levels in rat hippocampus - Toni-Lee Sterley; Fleur M. Howells; Jacqueline J. Dimatelis; Vivienne A. Russell (Metabolic Brain Disease, 2016)

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis - N. N. Basu; S. Ingham; J. Hodson; F. Lalloo; M. Bulman; A. Howell; D. G. Evans (Familial Cancer, 2015)

MITOsym®: A Mechanistic, Mathematical Model of Hepatocellular Respiration and Bioenergetics - Y. Yang; S. Nadanaciva; Y. Will; J. L. Woodhead; B. A. Howell; P. B. Watkins; S. Q. Siler (Pharmaceutical Research, 2015)

Enhancing the TurtleWatch product for leatherback sea turtles, a dynamic habitat model for ecosystem‐based management - Evan A. Howell; Aimee Hoover; Scott R. Benson; Helen Bailey; Jeffrey J. Polovina; Jeffrey A. Seminoff; Peter H. Dutton (Fisheries Oceanography, 2015)
Fishery management measures to reduce interactions between fisheries and endangered or threatened species have typically relied on static time‐area closures. While these efforts have reduced interactions, they can be costly and inefficient for managing highly migratory species such as sea turtles. The NOAA TurtleWatch product was created in 2006 as a tool to reduce the rates of interactions of loggerhead sea turtles with shallow‐set longline gear deployed by the Hawaii‐based pelagic longline fishery targeting swordfish. TurtleWatch provides information on loggerhead habitat and can be used by managers and industry to make dynamic management decisions to potentially reduce incidentally capturing turtles during fishing operations. TurtleWatch is expanded here to include information on endangered leatherback turtles to help reduce incidental capture rates in the central North Pacific. Fishery‐dependent data were combined with fishing effort, bycatch and satellite tracking data of leatherbacks to characterize sea surface temperature ( SST ) relationships that identify habitat or interaction ‘hotspots’. Analysis of SST identified two zones, centered at 17.2° and 22.9°C, occupied by leatherbacks on fishing grounds of the Hawaii‐based swordfish fishery. This new information was used to expand the TurtleWatch product to provide managers and industry near real‐time habitat information for both loggerheads and leatherbacks. The updated TurtleWatch product provides a tool for dynamic management of the Hawaii‐based shallow‐set fishery to aid in the bycatch reduction of both species. Updating the management strategy to dynamically adapt to shifts in multi‐species habitat use through time is a step towards an ecosystem‐based approach to fisheries management in pelagic ecosystems.

Applying association mapping and genomic selection to the dissection of key traits in elite European wheat - Alison R. Bentley; Marco Scutari; Nicolas Gosman; Sebastien Faure; Felicity Bedford; Phil Howell; James Cockram; Gemma A. Rose; Tobias Barber; Jose Irigoyen; Richard Horsnell; Claire Pumfrey; et al. (Theoretical and Applied Genetics, 2014)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Structural brain changes in prenatal methamphetamine-exposed children - Annerine Roos; Gaby Jones; Fleur M. Howells; Dan J. Stein; Kirsten A. Donald (Metabolic Brain Disease, 2014)

Breast cancer risk assessment in 8,824 women attending a family history evaluation and screening programme - D. Gareth R. Evans; Sarah Ingham; Sarah Dawe; L. Roberts; F. Lalloo; A. R. Brentnall; P. Stavrinos; Anthony Howell (Familial Cancer, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Unquantifiable uncertainty in projecting stock response to climate change: Example from North East Arctic cod - Daniel Howell; Anatoly A. Filin; Bjarte Bogstad; Jan Erik Stiansen (Marine Biology Research, 2013)

Dual-function theranostic nanoparticles for drug delivery and medical imaging contrast: perspectives and challenges for use in lung diseases - M. Howell; C. Wang; A. Mahmoud; G. Hellermann; S. S. Mohapatra; S. Mohapatra (Drug Delivery and Translational Research, 2013)

A review of potential image fusion methods for remote sensing-based irrigation management: part II - Wonsook Ha; Prasanna H. Gowda; Terry A. Howell (Irrigation Science, 2013)

A review of downscaling methods for remote sensing-based irrigation management: part I - Wonsook Ha; Prasanna H. Gowda; Terry A. Howell (Irrigation Science, 2013)

Climate-induced primary productivity change and fishing impacts on the Central North Pacific ecosystem and Hawaii-based pelagic longline fishery - Evan A. Howell; Colette C. C. Wabnitz; John P. Dunne; Jeffrey J. Polovina (Climatic Change, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Close-range hyperspectral imaging for geological field studies: workflow and methods - Tobias H. Kurz; Simon J. Buckley; John A. Howell (International Journal of Remote Sensing, 2013)

Platelet development in cuboid diamonds: insights from micro-FTIR mapping - D. Howell; C. J. O’Neill; K. J. Grant; W. L. Griffin; S. Y. O’Reilly; N. J. Pearson; R. A. Stern; T. Stachel (Contributions to Mineralogy and Petrology, 2012)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

In vitro to in vivo extrapolation and species response comparisons for drug-induced liver injury (DILI) using DILIsym™: a mechanistic, mathematical model of DILI - Brett A. Howell; Yuching Yang; Rukmini Kumar; Jeffrey L. Woodhead; Alison H. Harrill; Harvey J. Clewell; Melvin E. Andersen; Scott Q. Siler; Paul B. Watkins (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Statistical learning algorithms for identifying contrasting tillage practices with Landsat Thematic Mapper data - Pijush Samui; Prasanna H. Gowda; Thomas Oommen; Terry A. Howell; Thomas H. Marek; Dana O. Porter (International Journal of Remote Sensing, 2012)

Human In Vitro Models of Ischaemic Stroke: a Test Bed for Translation - Ana Antonic; Emily S. Sena; Geoffrey A. Donnan; David W. Howells (Translational Stroke Research, 2012)

Synergistic tonic and phasic activity of the locus coeruleus norepinephrine (LC-NE) arousal system is required for optimal attentional performance - Fleur M. Howells; Dan J. Stein; Vivienne A. Russell (Metabolic Brain Disease, 2012)

An All-Atom Model of the Structure of Human Copper Transporter 1 - Igor F. Tsigelny; Yuriy Sharikov; Jerry P. Greenberg; Mark A. Miller; Valentina L. Kouznetsova; Christopher A. Larson; Stephen B. Howell (Cell Biochemistry and Biophysics, 2012)

Estimating the carrying capacity of French Frigate Shoals for the endangered Hawaiian monk seal using Ecopath with Ecosim - Frank A. Parrish; Evan A. Howell; George A. Antonelis; Sara J. Iverson; Charles L. Littnan; James D. Parrish; Jeffrey J. Polovina (Marine Mammal Science, 2012)
The carrying capacity of the French Frigate Shoals (FFS) region for the endangered Hawaiian monk seal was appraised using an updated version of the original FFS Ecopath model ( Polovina 1984 ). Model parameters were updated using recent literature, and data from surveys of the seal population and its bottom‐associated prey. Together they produced a static mass balance model for 1998 when the prey surveys began. The Ecopath‐estimated monk seal biomass was 0.0045 t/km 2 , which was in close agreement with the biomass calculated from monk seal field beach counts (0.0046 t/km 2 ). Model simulations through time were done in Ecosim using the Ecopath balanced model and included fisheries data time series from 1998 to 2008. Monk seal biomass declined concurrently with decreases in benthic bottomfish biomass, which were influenced by large‐scale changes in the environment of the North Pacific. This model scenario was extended from 2010, when the last permitted fishery in the Northwestern Hawaiian Islands was closed, through to 2040, assuming a constant environmental signal. Model results for this time period did not show a recovery of monk seals that exceeded the initial 1998 model biomass levels, highlighting the importance of including environmental variability in estimates of monk seals recovery at FFS.

Development and characterization of 15 polymorphic tetranucleotide microsatellite loci for Townsend’s big-eared bat (Corynorhinus townsendii) and cross amplification in Rafinesque’s big-eared bat (Corynorhinus rafinesquii) - Dana N. Lee; Jenny M. Howell; Ronald A. Van Den Bussche (Conservation Genetics Resources, 2012)

Use of Data on Avian Demographics and Site Persistence during Overwintering to Assess Quality of Restored Riparian Habitat - STEVEN C. LATTA; CHRISTINE A. HOWELL; MARK D. DETTLING; RENÉE L. CORMIER (Conservation Biology, 2012)
Monitoring responses by birds to restoration of riparian vegetation is relatively cost‐effective, but in most assessments species‐specific abundances, not demography, are monitored. Data on birds collected during the nonbreeding season are particularly lacking. We captured birds in mist nets and resighted banded birds to estimate species richness and diversity, abundance, demographic indexes, and site‐level persistence of permanent‐resident and overwintering migrants in remnant and restored riparian sites in California. Species richness in riparian remnants was significantly higher than in restored sites because abundances of uncommon permanent residents were greater in remnants. Species richness of overwintering migrants did not differ between remnants and restored sites. Responses among overwintering migrants (but not permanent residents) to remnant and restored riparian sites differed. Capture rates were higher in remnant or restored riparian sites for 7 of 10 overwintering migratory species. For Lincoln's Sparrows (Melospiza lincolnii) and White‐crowned Sparrows (Zonotrichia leucophrys) proportions of older birds were significantly higher in remnants, even though capture rates of these species were higher in restored sites. Overwinter persistence of 4 migrant species was significantly higher in remnant than in restored sites. A higher proportion of Hermit Thrushes (Catharus guttatus, 56.3%), older Fox Sparrows (Passerella iliaca, 57.1%), Lincoln's Sparrows (59.7%), and White‐crowned Sparrows (67.8%) persisted in remnants than restored sites. Our results suggest restored riparian sites provide habitat for a wide variety of species in comparable abundances and diversity as occurs in remnant riparian sites. Our demographic and persistence data showed that remnants supported some species and age classes to a greater extent than restored sites.

Intrinsic and Extrinsic Temperature-Dependency of Viscosity-Sensitive Fluorescent Molecular Rotors - Sarah Howell; Marianna Dakanali; Emmanuel A. Theodorakis; Mark A. Haidekker (Journal of Fluorescence, 2012)

Erratum to: Quantifying strain birefringence halos around inclusions in diamond - D. Howell; I. G. Wood; D. P. Dobson; A. P. Jones; L. Nasdala; J. W. Harris (Contributions to Mineralogy and Petrology, 2011)

Pacific Atmospheric Sulfur Experiment (PASE): dynamics and chemistry of the south Pacific tropical trade wind regime - Alan Bandy; Ian C. Faloona; Byron W. Blomquist; Barry J. Huebert; Antony D. Clarke; Steven G. Howell; R. L. Mauldin; Christopher A. Cantrell; James G. Hudson; Brian G. Heikes; John T. Merrill; Yuhang Wang; et al. (Journal of Atmospheric Chemistry, 2011)

Breast cancer susceptibility variants alter risk in familial ovarian cancer - A. Latif; H. J. McBurney; S. A. Roberts; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Quantifying strain birefringence halos around inclusions in diamond - D. Howell; I. G. Wood; D. P. Dobson; A. P. Jones; L. Nasdala; J. W. Harris (Contributions to Mineralogy and Petrology, 2010)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)

RASSF1A polymorphism in familial breast cancer - J. Bergqvist; A. Latif; S. A. Roberts; K. D. Hadfield; F. Lalloo; A. Howell; D. G. Evans; W. G. Newman (Familial Cancer, 2010)

Oceanographic influences on the dive behavior of juvenile loggerhead turtles (Caretta caretta) in the North Pacific Ocean - Evan A. Howell; Peter H. Dutton; Jeffrey J. Polovina; Helen Bailey; Denise M. Parker; George H. Balazs (Marine Biology, 2010)

How can we improve information delivery to support conservation and restoration decisions? - Nathaniel E. Seavy; Christine A. Howell (Biodiversity and Conservation, 2010)

Panel of synaptic protein ELISAs for evaluating neurological phenotype - Paul E. Gottschall; Joanne M. Ajmo; Autumn K. Eakin; Matthew D. Howell; Hina Mehta; Lauren A. Bailey (Experimental Brain Research, 2010)

The Outcome of Unintentional Pediatric Bupropion Ingestions: A NPDS Database Review - Michael C. Beuhler; Henry A. Spiller; Howell C. Sasser (Journal of Medical Toxicology, 2010)

Non-timber forest product dependence among the Jah Hut subgroup of Peninsular Malaysia’s Orang Asli - Colleen J. Howell; Kurt A. Schwabe; Azizan Haji Abu Samah (Environment, Development and Sustainability, 2010)

Increased glutamate-stimulated release of dopamine in substantia nigra of a rat model for attention-deficit/hyperactivity disorder—lack of effect of methylphenidate - Fleur L. Warton; Fleur M. Howells; Vivienne A. Russell (Metabolic Brain Disease, 2009)

Evaluating eddy covariance cotton ET measurements in an advective environment with large weighing lysimeters - José Luis Chávez; Terry A. Howell; Karen S. Copeland (Irrigation Science, 2009)

Estimating hourly crop ET using a two-source energy balance model and multispectral airborne imagery - José Luis Chávez; P. H. Gowda; T. A. Howell; C. M. U. Neale; K. S. Copeland (Irrigation Science, 2009)

Comparing alternative systematic conservation planning strategies against a politically driven conservation plan - Christine N. Meynard; Christine A. Howell; James F. Quinn (Biodiversity and Conservation, 2009)

Radiometric surface temperature calibration effects on satellite based evapotranspiration estimation - J. L. Chávez; P. H. Gowda; T. A. Howell; K. S. Copeland (International Journal of Remote Sensing, 2009)

Sulfur dioxide in the tropical marine boundary layer: dry deposition and heterogeneous oxidation observed during the Pacific Atmospheric Sulfur Experiment - Ian Faloona; Stephen A. Conley; Byron Blomquist; Antony D. Clarke; Vladimir Kapustin; Steven Howell; Don H. Lenschow; Alan R. Bandy (Journal of Atmospheric Chemistry, 2009)

Distribution of Winter Flounder, Pseudopleuronectes americanus, in the Hampton–Seabrook Estuary, New Hampshire: Observations from a Field Study - Elizabeth A. Fairchild; James Sulikowski; Nathan Rennels; W. Huntting Howell; Christopher W. D. Gurshin (Estuaries and Coasts, 2008)

Remote sensing of contrasting tillage practices in the Texas Panhandle - Prasanna H. Gowda; T. A. Howell; S. R. Evett; J. L. Chavez; L. New (International Journal of Remote Sensing, 2008)

ET mapping for agricultural water management: present status and challenges - Prasanna H. Gowda; Jose L. Chavez; Paul D. Colaizzi; Steve R. Evett; Terry A. Howell; Judy A. Tolk (Irrigation Science, 2008)

Mapping of a gene (Vir) for a non-glaucous, viridescent phenotype in bread wheat derived from Triticum dicoccoides, and its association with yield variation - J. R. Simmonds; L. J. Fish; M. A. Leverington-Waite; Y. Wang; P. Howell; J. W. Snape (Euphytica, 2008)

HMG-CoA reductase is regulated by salinity at the level of transcription in Haloferax volcanii - Kelly A. Bidle; Thomas E. Hanson; Koko Howell; Jennifer Nannen (Extremophiles, 2007)

Using the composite variables of reproductive morphology, histology and steroid hormones to determine age and size at sexual maturity for the thorny skate Amblyraja radiata in the western Gulf of Maine - J. A. Sulikowski; J. Kneebone; S. Elzey; J. Jurek; W. H. Howell; P. C. W. Tsang (Journal of Fish Biology, 2006)
Age at size was linked to sexual maturity in 77 male and 93 female thorny skates Amblyraja radiata from the western Gulf of Maine using three criteria: 1) gross reproductive morphology, 2) histology and 3) steroid hormone concentrations. Age‐bias plots and the coefficient of variation from vertebral band counts suggested that the ageing method represented a non‐biased and precise approach to the age assessment of A. radiata . Maturity ogives for males, based on data gathered for clasper length, circulating testosterone concentrations and proportion of mature spermatocysts within the testes, predicted that 50% maturity occurred at a total length ( L T ) of 865 mm and c. 10·90 years of age. For females, maturity ogives, based on data gathered for ovary mass, shell gland mass, follicle size and circulating oestradiol concentrations, predicted that 50% maturity occurred at 875 mm L T and c. 11·00 years of age. Collectively, the results suggest that analysis of several contemporaneous reproductive variables offers an accurate determination of sexual maturity in the thorny skate.

El Niño effects in the Palmyra Atoll region: oceanographic changes and bigeye tuna ( Thunnus obesus ) catch rate variability - EVAN A. HOWELL; DONALD R. KOBAYASHI (Fisheries Oceanography, 2006)
A generalized additive model (GAM) was constructed to separate and quantify the effects of fishery‐based (operational) and oceanographic parameters on the bigeye tuna ( Thunnus obesus ) catch rates at Palmyra Atoll in the central Tropical Pacific. Bigeye catch, the number of hooks per set, and set location from 4884 longline sets spanning January 1994 to December 2003 were used with a temporally corresponding El Niño‐Southern Oscillation (ENSO) indicator built from sea surface height (SSH) data. Observations of environmental data combined with the results from the GAM indicated that there is an increase in bigeye catch rates corresponding to an increase in eastward advection during the winter months of El Niño events. A seasonal pattern with higher bigeye catch rates from December to April and a spatial pattern with higher rates to the northeast and northwest of the atoll were observed during this study period. It is hypothesized that the combination of the eastward advection of the warm pool coupled with vertical changes in temperature during the winter months of El Niño events increases the availability of bigeye tuna in this region. This increase in availability may be due to a change in exploitable population size, location, or both.

Indole-3-carbinol-induced death in cancer cells involves EGFR downregulation and is exacerbated in a 3D environment - E. P. Moiseeva; L. H. Fox; L. M. Howells; L. A. F. Temple; M. M. Manson (Apoptosis, 2006)

Does the mitochondrial genome play a role in the etiology of Alzheimer’s disease? - Joanna L. Elson; Corinna Herrnstadt; Gwen Preston; Leon Thal; Christopher M. Morris; J. A. Edwardson; M. Flint Beal; Douglass M. Turnbull; Neil Howell (Human Genetics, 2006)

Ordered Assembly of Mitochondria During Rice Germination Begins with Promitochondrial Structures Rich in Components of the Protein Import Apparatus - Katharine A. Howell; A. Harvey Millar; James Whelan (Plant Molecular Biology, 2006)

Age and size at sexual maturity for the winter skate, Leucoraja ocellata, in the western Gulf of Maine based on morphological, histological and steroid hormone analyses - James A. Sulikowski; Paul C. W. Tsang; W. Huntting Howell (Environmental Biology of Fishes, 2005)

How much do valley fills influence headwater streams? - Kyle J. Hartman; Michael D. Kaller; John W. Howell; John A. Sweka (Hydrobiologia, 2005)

Factors affecting the post‐release survival of cultured juvenile Pseudopleuronectes americanus - E. A. Fairchild; W. H. Howell (Journal of Fish Biology, 2004)
Laboratory experiments were performed with cultured and wild juvenile winter flounder Pseudopleuronectes americanus to evaluate differences in behaviour and adaptation affecting post‐release vulnerability to predation. Studies revealed that the cryptic abilities of cultured winter flounder increased over time. Sediment‐naïve, cultured fish required a minimum of 2 days to improve their burying skills and at least 90 days for colour adaptation to match the sediment. Cultured winter flounder selected sediments consisting of small grains and colours matching their own pigment. Cultured winter flounder, regardless of their colour, were significantly more vulnerable to predation by birds. Additionally, cultured fish reacted differently than wild winter flounder when exposed to cues from a potential predator.

An annual cycle of steroid hormone concentrations and gonad development in the winter skate, Leucoraja ocellata , from the western Gulf of Maine - J. A. Sulikowski; P. C. W. Tsang; W. Huntting Howell (Marine Biology, 2004)

Reproductive isolation among morphotypes of the Atlantic seastar species Zoroaster fulgens (Asteroidea: Echinodermata) - Kerry L. Howell; Alex D. Rogers; Paul A. Tyler; David S. M. Billett (Marine Biology, 2004)

Aquatic Snails from Mining Sites Have Evolved to Detect and Avoid Heavy Metals - H. Lefcort; D. P. Abbott; D. A. Cleary; E. Howell; N. C. Keller; M. M. Smith (Archives of Environmental Contamination and Toxicology, 2004)

Forage and migration habitat of loggerhead ( Caretta caretta ) and olive ridley ( Lepidochelys olivacea ) sea turtles in the central North Pacific Ocean - Jeffrey J. Polovina; George H. Balazs; Evan A. Howell; Denise M. Parker; Michael P. Seki; Peter H. Dutton (Fisheries Oceanography, 2004)
Satellite telemetry from 26 loggerhead ( Caretta caretta ) and 10 olive ridley ( Lepidochelys olivacea ) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28–40°N, and occupy sea surface temperatures (SST) of 15–25°C. Their dive depth distribution indicated that they spend 40% of their time at the surface and 90% of their time at depths

Avoiding Pitfalls of Using Species Distribution Models in Conservation Planning - BETTE A. LOISELLE; CHRISTINE A. HOWELL; CATHERINE H. GRAHAM; JAQUELINE M. GOERCK; THOMAS BROOKS; KIMBERLY G. SMITH; PAUL H. WILLIAMS (Conservation Biology, 2003)
Museum records have great potential to provide valuable insights into the vulnerability, historic distribution, and conservation of species, especially when coupled with species‐distribution models used to predict species' ranges. Yet, the increasing dependence on species‐distribution models in identifying conservation priorities calls for a more critical evaluation of model robustness. We used 11 bird species of conservation concern in Brazil's highly fragmented Atlantic Forest and data on environmental conditions in the region to predict species distributions. These predictions were repeated for five different model types for each of the 11 bird species. We then combined these species distributions for each model separately and applied a reserve‐selection algorithm to identify priority sites. We compared the potential outcomes from the reserve selection among the models. Although similarity in identification of conservation reserve networks occurred among models, models differed markedly in geographic scope and flexibility of reserve networks. It is essential for planners to evaluate the conservation implications of false‐positive and false‐negative errors for their specific management scenario before beginning the modeling process. Reserve networks selected by models that minimized false‐positive errors provided a better match with priority areas identified by specialists. Thus, we urge caution in the use of models that overestimate species' occurrences because they may misdirect conservation action. Our approach further demonstrates the great potential value of museum records to biodiversity studies and the utility of species‐distribution models to conservation decision‐making. Our results also demonstrate, however, that these models must be applied critically and cautiously.

Fluid Regulation and Physiological Adjustments in the Winter Skate, Leucoraja ocellata, Following Exposure to Reduced Environmental Salinities - James A. Sulikowski; Jason R. Treberg; W. Huntting Howell (Environmental Biology of Fishes, 2003)

Respiratory gene expression in soybean cotyledons during post-germinative development - Daniel O. Daley; Michael J. Considine; Katharine A. Howell; A. Harvey Millar; David A. Day; James Whelan (Plant Molecular Biology, 2003)

Monitoring the Penetration Enhancer Dimethyl Sulfoxide in Human Stratum Corneum in Vivo by Confocal Raman Spectroscopy - Peter J. Caspers; Adrian C. Williams; Elizabeth A. Carter; Howell G. M. Edwards; Brian W. Barry; Hajo A. Bruining; Gerwin J. Puppels (Pharmaceutical Research, 2002)

Arsenic uptake and accumulation in rice (Oryza sativa L.) irrigated with contaminated water - Md. Joinal Abedin; J. Cotter-Howells; Andy A. Meharg (Plant and Soil, 2002)

A candidate gene for congenital bilateral isolated ptosis identified by molecular analysis of a de novo balanced translocation - Tristan F. McMullan; John A. Crolla; Simon G. Gregory; Nigel P. Carter; Rachel A. Cooper; Gareth R. Howell; David O. Robinson (Human Genetics, 2002)

Arabidopsis mutants with increased organ regeneration in tissue culture are more competent to respond to hormonal signals - Andrew Cary; Shyam J. Uttamchandani; Rafaël Smets; Harry A. Van Onckelen; Stephen H. Howell (Planta, 2001)

Heterogeneity of RMA-S cell line: derivatives of RMA-S cells lacking H2-K b and H2-D b expression - Dewey Howell; Jonathan M. Levitt; Patricia A. Foster; Margaretha M. Guenther; Said M. Shawar; Robert R. Rich; John R. Rodgers (Immunogenetics, 2000)

Modelling the influence of glacial isostasy on Late Weichselian ice-sheet growth in the Barents Sea - Daniel Howell; Martin J. Siegert; Julian A. Dowdeswell (Journal of Quaternary Science, 2000)

A suite of highly polymorphic microsatellite markers in turbot ( Scophthalmus maximus L.) with potential for use across several flatfish species - A. Iyengar; S. Piyapattanakorn; D. A. Heipel; D. M. Stone; B. R. Howell; A. R. Child; N. Maclean (Molecular Ecology, 2000)

Evaluation of the Distribution of Mercury in Lakes in Nova Scotia and Newfoundland (Canada) - O. C. Vaidya; G. D. Howell; D. A. Leger (Water, Air, & Soil Pollution, 2000)

Lobster movements in an estuary - W. H. Watson III; A. Vetrovs; W. H. Howell (Marine Biology, 1999)

Evaluation of crop water stress index for LEPA irrigated corn - Attila Yazar; T. A. Howell; D. A. Dusek; K. S. Copeland (Irrigation Science, 1999)

Analysis of sheep T-cell receptor β-chain heterogeneity - Wayne A. Halsey; Brent E. Palmer; James C. DeMartini; M. D. Howell (Immunogenetics, 1999)

Functions of the white and topaz loci of Lucilia cuprina in the production of the eye pigment xanthommatin - K. M. Summers; A. J. Howells (Biochemical Genetics, 1980)

Isolation and biochemical analysis of a temperature-sensitive scarlet eye color mutant of Drosophila melanogaster - A. J. Howells (Biochemical Genetics, 1979)

Xanthommatin biosynthesis in wild-type and mutant strains of the Australian sheep blowfly Lucilia cuprina - K. M. Summers; A. J. Howells (Biochemical Genetics, 1978)

Control of drosopterin synthesis in Drosophila melanogaster: Mutants showing an altered pattern of GTP cyclohydrolase activity during development - B. A. Evans; A. J. Howells (Biochemical Genetics, 1978)

Developmental patterns of 3-hydroxykynurenine accumulation in white and various other eye color mutants of Drosophila melanogaster - A. J. Howells; K. M. Summers; Rosemary L. Ryall (Biochemical Genetics, 1977)

The ommochrome biosynthetic pathway in Drosophila melanogaster: The head particulate phenoxazinone synthase and the developmental onset of xanthommatin synthesis - M. Yamamoto; A. J. Howells; Rosemary L. Ryall (Biochemical Genetics, 1976)

A biochemical study of the scarlet eye-color mutant of Drosophila melanogaster - A. J. Howells; Rosemary L. Ryall (Biochemical Genetics, 1975)

Levels of RNA and DNA in Drosophila melanogaster at different stages of development: A comparison between one bobbed and two phenotypically non-bobbed stocks - A. J. Howells (Biochemical Genetics, 1972)